Analisis Faktor Yang Mempengaruhi Perilaku Hidup Bersih Sehat Pada Anak Usia Sekolah Dasar: Literature Review - Rowdlatul Jannah Nurochman, Putri; Balaputra, Ishana (STIKES Ngesti Waluyo, 2024)
The health condition of children in the world, especially in Indonesia, is still relatively low compared to ASEAN countries, such as Malaysia, Philippines, Thailand, Singapore, Brunei Darussalam and Vietnam. Indonesia is a developing country that still faces various health problems, including clean and healthy behaviour. The low level of implementation of PHBS in children means that children tend to get sick quickly, and they are also a group that is very vulnerable to disease. The purpose of writing this literature review is to look at the factors that most influence the implementation of PHBS in children. This research data was taken from four relevant databases, PubMed, Science Direct, EBSCO and Google Scholar, using the PIOS (Participant, Intervention, Outcomes and Study Design) method and MeSH terms in the search engine. The data are taken from journals published in 2020-2024, in English and Indonesian (open access and full text) and original articles. Of the 918 articles found, only eight (8) articles met the inclusion criteria. The results of this literature review explain that several factors influence clean and healthy living behaviour, namely parenting patterns, attitudes, level of knowledge, and the role of health workers. Of these several factors, one factor is most dominant in implementing children's clean-living behaviour, namely the parenting style factor.